The Use of Meme as A Representation of Public Opinion in Social Media: A Case Study of Meme About Bekasi in Path and Twitter - Handayani, Fitrie; Sari, Siti Dewi Sri Ratna; Respati, Wira (Bina Nusantara University, 2016)
Article aimed at exploring the connection between meme in social media and public opinion representation. Object examined in this study was the meme about the social condition in Bekasi. A qualitative descriptive method was applied to analyze issues that are expressed by meme about Bekasi and the motivation of distributing them in social media. The result shows that opinion expressed in meme could carry more than one issues, such as distance, bad traffic, extreme hot temperature, and damaged roads. The motivation of using meme is because it is funny, easily understood, and more likely to get a response. The result also shows that responding to a meme by retweeting or repathing do not necessarily mean agreement with the issues.